Bromate in Sudanese Bottled Water (University of Khartoum Engineering Journal, 2022)
The objective of this paper is to monitor bromate in bottled water due to the fact that Long-termexposure to bromate may increase consumers’ risk of cancer(1,3), random samples fromtap waterand differentbottledbrands were analyzed for bromate content and their physical properties. The obtained results revealed thatbromate content exceeds the SSMO ,FDA AND IBWA limits of maximum content not exceeding 10 ppb in threesamples, although two of them were taken from the same aquifer which eliminates the source factor and indicatesthat the main reason is the ozonation process employed in the disinfection of water. The study recommended toreduce ozone quantity and contact time In addition to the avoidance of direct sunlight exposure which willencourage liquid or gaseous chlorine to generatephoto activation bromate in bromide-containing water.It is alsoimportant to introduce safer technologies like membrane or iron exchange filtration.